UJI TOKSISITAS AKUT EKSTRAK ETANOL KAYU MANIS - Syahdiana Waty; Nurul Hidayah (Poltekkes Kemenkes Medan, 2023)
Cinnamon bark (Cinnamomum burmanni) is one of the cheap and easy traditional medicinal herbs and is widely used to treat toothache. The largest content of cinnamon bark is essential oil which contains the main compounds cinnamaldehyde (60.72%), eugenol (17.62%) and coumarin (13.39%). The content has potential as an antibacterial. Cinnamon bark extract affects the growth of Streptococcus mutans which is the main bacterium that causes dental caries (Puspita et al., 2013). This research was continued to the toothpaste formulation stage where people can use this plant as an anti-plaque comfortably. The development of extracts into paste preparations requires safety or toxicity data within a certain period of time. This study uses an experimental design. The test rats were divided into 4 groups consisting of the normal group (CMC Na 0.5%), the EEKM group at doses of 300 mg/kg BW, 2000 mg/kg BW and 5000 mg/kg BW. Toxic symptoms observed included behavioral changes such as tremors, slow walking, urination, defecation, motor ability tests such as stage tests, catalepsy, hanging and death. Changes in toxic symptoms were observed intensively every 30 minutes in the first 2 hours after administration of the test preparation and followed up to 14 days after administration. Based on the results of the study showed that EEKM at doses of 300 mg/kg BW, 2000 mg/kg BW and 5000 mg/kg BW did not show a toxic effect on the physical behavior of the test animals. EEKM is included in the practically non-toxic criteria, where at a dose of 5000 mg/kg bb there is no death, the LD50 value is greater than 5000 so it is included in the practically non-toxic criteria.